"Who's the Student at Home?": Parental Help-Giving Orientation in Learning at Home Predicted using a Parent's Personal Characteristics - Gal Harpaz; Yael Grinshtain; Yosi Yaffe (MDPI AG, 2024)
The present study focuses on the involvement of a parent in their child's learning processes, particularly, their help-giving orientation while learning at home. The main goal of the study was to identify the connection between the parent's personal characteristics and the help-giving orientation the parent provides to their child: autonomous vs. dependent (parent as student) help-giving. The sample was collected using online participant recruitment surveys in Israel. In total, 306 parents aged 27-59, who had at least one child in elementary school, answered five questionnaires measuring the research variables: the short grit scale; the satisfaction with life scale; the advice/affect management-overparenting subscale; the parenting sense of competence scale; the parental help-giving orientations scale (PHGOs), and a background questionnaire. The findings identified negative associations between parental personal characteristics (grit, advice/affect management, well-being) and parent-as-student orientation and positive associations between the parent's characteristics and parental autonomous help-giving orientation, with all of these effects at least partially mediated by parental self-efficacy (indirect effects). The results provide greater insight into the relationship between a parent's personal characteristics and their choice of assistance to their child and contribute to the knowledge regarding parental involvement in learning at home and educational contexts in general.